Factors affecting the availability of hybrid cerebral and myocardial revascularization - R. S. Tarasov; A. I. Danilovich (Кардиоваскулярная терапия и профилактика)
Aim. To analyze factors affecting the availability of hybrid cerebral and myocardial revascularization by synchronous percutaneous coronary intervention (PCI) and carotid endarterectomy (CEA).Material and methods. This retrospective study included 263 patients with coronary and internal carotid artery involvement undergoing PCI and CEA during the period from 2011 to 2017.Results. The study revealed the following factors increasing the availability of revascularization: hybrid cerebral and myocardial revascularization, successful PCI using drug-eluting stents, postPCI TIMI flow grade 3, and radial access for PCI. The following factors reduced the availability: polyvascular disease >50% in three beds, prior PCI, left ventricular ejection fraction <50%, left coronary artery involvement, living without a family, staged revascularization, CEA before PCI, unsuccessful/complicated PCI with post-PCI TIMI flow grades of 0-1, residual SYNTAX score >9, emergency hospitalization and multiple emergency PCI of the coronary arteries in the long-term follow-up period.Conclusion. Comprehensive analysis of clinical, demographic, anatomical, angiographic, and perioperative factors made it possible to identify predictors that affect the availability of hybrid revascularization.